2004
DOI: 10.1039/b405789a
|View full text |Cite
|
Sign up to set email alerts
|

High-field EPR study and crystal and molecular structure of trans-RSSR-[CrCl2(cyclam)]nX (X = ZnCl42−, Cland Cl·4H2O·0.5HCl)

Abstract: For the first time, HF-EPR (94.5 GHz) spectroscopy has been used to determine crystal field parameters in chromium(III) coordination compounds. The large zero-field splitting parameters of the dark-green photochromic trans-RSSR-[CrCl(2)(cyclam)](2)ZnCl(4), 1, the red-purple trans-RSSR-[CrCl(2)(cyclam)]Cl, 2, and the red-purple trans-RSSR-[CrCl(2)(cyclam)]Cl.4H(2)O.0.5HCl, 3, where cyclam = 1,4,8,11-tetraazacyclotetradecane, have been obtained. A full analysis of EPR spectra at 94.5 GHz of diluted complexes 1, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
14
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 29 publications
4
14
1
Order By: Relevance
“…The two notions CFPs and ZFSPs have been evidently considered as synonymous by Solano-Peralta et al [142]. The ZFSPs appearing in their SH as well as several times in text were correctly named as, e.g.…”
Section: Confusion Between the Cf (Lf) And Sh (Zfs) Quantities In Thementioning
confidence: 97%
See 1 more Smart Citation
“…The two notions CFPs and ZFSPs have been evidently considered as synonymous by Solano-Peralta et al [142]. The ZFSPs appearing in their SH as well as several times in text were correctly named as, e.g.…”
Section: Confusion Between the Cf (Lf) And Sh (Zfs) Quantities In Thementioning
confidence: 97%
“…'zero-field splitting: axial (D) and rhombic (E) components'. However, in Abstract it is stated, quote [142]: 'For the first time, HF-EPR (94.5 GHz) spectroscopy has been used to determine crystal field parameters in chromium(III) coordination compounds. The large zero-field splitting parameters of… have been obtained' and 'the crystal field is mainly rhombic'.…”
Section: Confusion Between the Cf (Lf) And Sh (Zfs) Quantities In Thementioning
confidence: 99%
“…(1) Confusion between the CF (LF) and SH (ZFS) quantities, mainly the CF=ZFS confusion exemplifi ed by consideration of the two notions: the CF parameters (CFPs) and the ZFS parameters evidently as synonymous, occurs in recent EMR--related papers, e.g., [22][23][24][25][26][27][28][29][30][31][32]; for critical comments, see [14]. Apart from the problems and confusions identifi ed in the review on molecular magnets [16], serious forms of the CF=ZFS confusion occur also in the EMR and SMM/MNM related textbook [13].…”
Section: Summary Of Emr-related Problemsmentioning
confidence: 99%
“…Very recently, it has been found that the differences in the magnetic and optical properties of the trans-RSSR-[CrCl 2 (cyclam)] n X n , when X = Cl À , ZnCl 2À 4 compounds, have been attributed to supramolecular interactions between the chromium cations and the ZnCl 2À 4 [1][2][3]. On the other hand, from luminescence studies of the double salt [Cr(en) 3 ][Cr(CN) 6 ] AE XH 2 O, it has been reported that an energy transfer occurs because lifetime of the 2 E g state of donor [Cr(en) 3 ] 3+ (6.0 ns) is in agreement with rise time of the 2 E g state of acceptor [Cr(CN) 6 ] 3À (6.2 ns) [4].…”
mentioning
confidence: 99%
“…Within a project about the characterisation of the counterion role in the explanation of the photochromism exhibited by trans-RSSR-[CrCl 2 (cyclam)] 2 ZnCl 4 [1,2] and in order to understand which are the factors that are affecting this property, we synthesised and characterised by X-ray diffraction the trans-[CrCl 2 (cyclam)] 3 [Cr(CN) 6 ] AE 14H 2 O. We also carried out a photoluminescence study on this compound.…”
mentioning
confidence: 99%